Health Inequities in Orthopaedic Trauma Surgery in the United States: A Scoping Review. Issue 9 (1st May 2023) - Lee, Chase; Ezell, Kade; Dunford, Bryan; Nees, Danya; Jacobsen, Samuel M.; Staggs, Jordan; Checketts, Jake; Vassar, Matt
Abstract : Background: Health inequities have been shown to have negative effects on patient care and the healthcare system. It is important for orthopaedic trauma surgeons and researchers to understand the extent to which patients are affected by these inequities. Methods: We conducted a scoping review as outlined by the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist. We searched PubMed and Ovid Embase for articles relating to orthopaedic trauma surgery and health inequities. Results: After exclusion criteria were applied, our final sample consisted of 52 studies. The most frequently evaluated inequities were sex (43 of 52 [82.7]), race/ethnicity (23 of 52 [44.2]), and income status (17 of 52 [32.7]). The least frequently evaluated inequities were lesbian, gay, bisexual, transgender, and queer identity (0 of 52 [0.0]) and occupational status (8 of 52 [15.4]). Other inequities evaluated included rural/underresourced (11 of 52 [21.1]) and educational level (10 of 52 [19.2]). No trend was observed when examining inequities reported by year. Conclusion: Health inequities exist in orthopaedic trauma literature. Our study highlights multiple inequities in the field that need further investigation. Understanding current inequities and how to best mitigate them could improve patient care and outcomes in orthopaedic trauma surgery.